Aluminium recovery from water treatment sludge under different dosage of sulphuric acid. (November 2019) - Hassan Basri, M H; Mohammad Don, N N; Kasmuri, N; Hamzah, N; Alias, S; Azizan, F A
Abstract: Aluminium sulphate Al2(SO4)3 known as alum is commonly added chemical in coagulation-flocculation process in water treatment plants. Despite of its effectiveness in treating the water, it produces high volume of residual alum sludge to be discarded to sludge lagoon. Therefore, sludge disposal is one of the main drawbacks in water treatment plants as it requires large footprints to store the residual sludge before being dumped at landfills. The sludge still contains high concentrations of aluminium that can be recovered for further use. Acidification process using sulphuric acid is investigated in this study to recover the aluminium from sludge. Different dosage of sulphuric acid ranges at 0.45 – 1.80M at constant weight of alum sludge at 300g were analysed to obtain the maximum percentages of aluminium recovery. Inductively coupled plasma optical emission spectrometry (ICP-OES) was used to analyse the recovered aluminium concentration. Besides the element of aluminium, other elements such as Ferum (Fe), Calcium (Ca) and Potassium (K) were also recovered through the acidification process. It was found that element of aluminium shows the highest concentration. The optimum recovery of aluminium was attained at alum sludge 300g and dosage of 1.35M sulphuric acid in which the recovery ratio at up to 98%. This shows that the aluminium present at high concentration in the sludge and if the sludge is dumped at landfills, the remaining aluminium will affect the environment. Furthermore, it is recommended that the recovered aluminium from water treatment sludge has the potential to be an alternative coagulant element in water treatment process.